Ketatanegaraan Pada Masa Dinasti Fathimiyah: Studi Terhadap Pengaruh Syi'ah Terhadap Sistem Pemerintahan - Pratama, M.Amri; Zega, Madan Syairazi; Sitepu, Ahmad Nubli; Arbi, Muhammad; Rizki, Muhammad Fakhri (Tabayyun : Journal Of Islamic Studies, 2023)
The Shiffin War in 657 AD caused divisions among Muslims. This war ended with arbitration which was not accepted by Ali bin Abi Talib, thus triggering a split into three political factions, namely the Khawarij, Muawiyah and Shiite groups. The Shiites believe that Ali bin Abi Talib was the elected caliph and the first imam after the Prophet Muhammad SAW. They believe that the highest leadership in Islam is the imam, not the caliph. The concept of imamate in the Shiite school of thought is based on the belief that Ali bin Abi Talib is the heir of the Prophet Muhammad SAW. The Shiite sect is divided into several groups, including Shiite Imamiyah, Shiite Ismailiyah, and Shiite Zaidiyah. Each group has a different view of the imamate. Shiite Imamiyah and Shiite Ismailiyah do not recognize the leadership of Abu Bakr, Umar and Uthman. However, the Zaidiyah Shiites recognize the leadership of Abu Bakr, Umar, and Uthman, but only as caliphs, not imams. During its heyday, the Shiite school of thought was able to build a civilization and contribute to Islamic civilization. One example is the Fatimid dynasty which ruled Egypt in the 10th to 12th centuries AD.